Biomimetic Nanobomb for Synergistic Therapy with Inhibition of Cancer Stem Cells. Issue 12 (1st January 2023) - Liu, Shuang; Zhang, Tianshu; Li, Shanshan; Wu, Qingyuan; Wang, Kexin; Xu, Xican; Lu, MingZhu; Shao, Rongguang; Zhao, Wuli; Liu, Huiyu
Abstract: Cancer stem cells (CSCs), a type of cell with self‐renewal, unlimited proliferation, and insensitivity to common physical and chemical factors, are the key to cancer metastasis, recurrence, and chemo‐resistance. Available CSCs inhibition strategies are mainly based on small molecule drugs, yet are limited by their off‐target toxicity. The link between CSCs and non‐CSCs interconversion is difficult to sever. In this work, a nanotherapeutic strategy based on MnOx ‐loaded polydopamine (MnOx /PDA) nanobombs with chemodynamic, photodynamic, photothermal and biodegradation properties to inhibit CSCs and non‐CSCs concurrently is reported. The MnOx /PDA nanobombs can directly disrupt the microenvironment and tumorigenic capacity of CSCs by generating hyperthermia, oxidative stress and alleviating hypoxia. The markers of CSCs are subsequently downregulated, leading to the clearance of CSCs. Meanwhile, the synergistic therapy mediated by MnOx /PDA nanobombs can directly ablate the bulk tumor cells, thus cutting off the supply of CSCs transformation. For tumor targeting, MnOx /PDA is coated with macrophage membrane. The final tumor inhibition rate of the synergistic therapy is 70.8% in colorectal cancer (CRC) model. Taken together, the present work may open up the exploration of nanomaterial‐based synergistic therapy for the simultaneous elimination of therapeutically resistant CSCs and non‐CSCs. Abstract : Manganese oxide (MnOx ) loaded polydopamine nanobombs (MnOx /PDA) are prepared for the synergistic phototherapy/chemodynamic therapy, and cancer hypoxia relief, which can kill cancer cells and inhibit cancer stem cells (CSCs) simultaneously. MnOx /PDA coated by macrophage membrane exhibit superior targeting ability in vivo, and realize tumor inhibition and cancer stemness suppression in colorectal cancer model.